PROFILE OF PATIENTS WITH UROLITHIASIS IN RSUP DR. M. DJAMIL IN 2022 - Hanif, Pandu Muhammad; Zulfiqar, Yevri; Windasari, Noverika; Alvarino; Rustam, Erlina; Arisanty, Dessy (Indonesian Urological Association, 2026)
Introduction: Urolithiasis or urinary stone refers to the stone formation along the urinary tract, from the kidney to the urethra. Urolithiasis prevalence is known to differ across continents and across the country. A study in Indonesia in 2013 reported a national prevalence of 0.6% and a regional prevalence 0.4% in West Sumatra. Objective: This study aimed to determine patients characteristics and provide an overview of stone distribution among patients with urolithiasis at RSUP Dr. M. Djamil Padang. Material & Methods: This study was a descriptive observational research with a cross-sectional design using medical record data of patients with urolithiasis in RSUP Dr. M. Djamil Padang during January - July 2022. A total sampling method was used to collect data from 273 patients. Results: This research showed that most of the patients were males (58.24%) and aged between 51 - 60 years old (34.43%). The stones found were more commonly located in the upper urinary tract, comprising the kidney (73.26%) and ureter (14.65%). Conclusion: This study concluded that male was more likely to develop urolithiasis than female, and so did people aged 51 - 60 years old compared to the other age range. The stone’s location was more likely to occur in the kidney. Keywords: Urolithiasis, patients characteristics, stone’s location.